Analisis Hukum terhadap Aturan Hukum Penanaman Modal Asing dalam Mendorong Investasi di Indonesia - Sri Nurnaningsih Rachman; Herry M Polontoh; Jesslyn Elisandra Harefa; Amstrong Harefa; Tora Yuliana (Jurnal Hukum Lex Generalis, 2025)
Foreign direct investment (FDI) is a vital element in supporting national economic development, especially in increasing productivity, encouraging strategic sector growth, and strengthening Indonesia's position in global economic competition. Normatively, Indonesia has established a legal basis through Law No. 25/2007 on Investment, as well as various implementing regulations such as Presidential Regulations and BKPM Regulations that aim to provide certainty, protection, and convenience for foreign investors. This research aims to analyze the extent to which these legal regulations are able to create a conducive investment climate and identify legal constraints that arise in their implementation. This research uses normative juridical method with legislative approach and literature review. The results show that although Indonesia's FDI legal framework has been quite progressive, in practice it is still faced with a number of serious problems such as inter-regulatory unsynchronization, complicated licensing bureaucracy, weak legal protection for investors, and policy fluctuations due to political pressure and sectoral interests. These conditions create legal uncertainty and reduce Indonesia's competitiveness in the eyes of global investors. Therefore, regulatory harmonization, bureaucratic reform, and policy consistency are needed to strengthen the effectiveness of foreign investment law in Indonesia.